Extraction and partial purification of protease from Bilimbi (Averrhoa bilimbi L.) / Normah Ismail and Nur' Ain Mohamad Kharoe - Ismail, Normah; Mohamad Kharoe, Nur' Ain (Research Management Institute (RMI), 2013)
Unripe and ripe bilimbi (Averrhoa bilimbi L.) were ground and the extracted juices were partially purified by ammonium sulfate precipitation at the concentrations of40 and 60% (w/v). The collected proteases were analysed for pH, temperature stability, storage stability, molecular weight distribution, protein concentration and protein content. Protein content of bilimbi fruit was 0.89 g. Protease activity ofboth the unripe and ripe fruit were optimum at pH 4 and 40°C when the juice were purified at 40 and 60% ammonium sulfate precipitation. A decreased in protease activity was observed during the seven days of storage at 4°C. Molecular weight distribution indicated that the proteases protein bands fall between 10 to 220 kDa. Protein bands were observed at 25, 50 and 160 kDa in both the unripe and ripe bilimbi proteases purified with 40% ammonium sulfate, however, the bands were more intense in those from unripe bilimbi. No protein bands were seen in proteases purified with 60% ammonium sulfate. Protein concentration was higher for proteases extracted with 40% ammonium sulfate at both ripening stages. Thus, purification using 40% ammonium sulfate precipitation could be a successful method to partially purify proteases from bilimbi especially from the unripe stage.